Attitudes of Physical Education Teachers toward the Inclusion of Students with Disabilities in Typical Classes - Vaporidi Ιωάννα; Kokaridas ∆ηµήτριος; Krommidas Χαράλαµπος (Inquiries in Physical Education and Sport, 2005)
The purpose of this study was to examine the attitudes of Greek physical education teachers toward the inclusion of students with disabilities in regular education settings and to compare the results with the findings of similar studies. Participants were 54 physical education teachers working at different schools of Trikala region. Each participant completed the Teachers Integration Attitudes Questionnaire (Sideridis & Chandler, 1997), which assesses scores for four factors: skills, benefits, acceptance and support. The results of the study showed that the attitudes of physical education teachers toward the inclusion of students with disabilities in their regular classes are related to the level of knowledge that the teachers believe they have for the special needs conditions. Encouraging is the finding that physical education teachers expressed their willingness to broaden their knowledge concerning people with special needs. However, they doubted that inclusion could succeed, due to lack of appropriate support services, professional training and material - technical infrastructure.